2004
DOI: 10.1063/1.1751226
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser nanostructuring of nickel thin films for the catalytic growth of carbon nanotubes

Abstract: Pulse laser ablation and subsequent laser nanostructuring at room temperature has been employed to produce nanostructured Ni on SiO 2 /Si substrates for catalytic growth of carbon nanotubes. The resultant nanostructured surface is seen to consist of nanometer sized hemispherical droplets whose mean diameter is controlled by the initial metal thickness, which in turn is readily controlled by the number of laser pulses. Vertically aligned multiwall carbon nanotube mats were then grown using conventional plasma e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
4
51
0
Order By: Relevance
“…Previously, we demonstrated that ELN of thin Ni films can be used to produce nanoscopic Ni catalyst particles suitable for the growth of carbon nanotubes. 16 Here we examine the underlying mechanisms of the ELN technique more closely, for a carefully chosen selection of metals with differing physical and thermodynamic properties, and differing enthalphies of formation for the oxide. We discuss how this process differs from the traditional thermal annealing method of producing nanostructured metal-on-oxide substrates and compare the experimental data obtained during ELN of thin metal films with simulations of the heat transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that ELN of thin Ni films can be used to produce nanoscopic Ni catalyst particles suitable for the growth of carbon nanotubes. 16 Here we examine the underlying mechanisms of the ELN technique more closely, for a carefully chosen selection of metals with differing physical and thermodynamic properties, and differing enthalphies of formation for the oxide. We discuss how this process differs from the traditional thermal annealing method of producing nanostructured metal-on-oxide substrates and compare the experimental data obtained during ELN of thin metal films with simulations of the heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles and other metal nanostructures are the basic building blocks in photonics research 12 and it is expected that magnetic nanoparticles will have a dramatic impact on high density magnetic recording 13 and radarabsorbing composite applications. 14 Transition metal nanoparticles, such as Ni, Co, Fe, and Au are of considerable importance for the catalytic growth of nanostructures including carbon nanotubes 11,15,16 and silicon nanowires. 17 Nanoparticle systems are also of significant interest to the fuel cell community, working to increase the reaction surface for a fixed cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pulsed-laser processing is an ultrafast process and can be performed in ambient atmosphere. 20,22,23 In this study, we demonstrated a method using pulsed excimer laser to generate NiSO 4 nanoparticles as catalysts for CNF/CNT growth. CNTs grown from nanocatalysts, which were generated under optimized laser parameters, were highly uniform in diameters.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Nanocatalysts were fabricated by excimer laser ablation of thin transitional metal films for CNT growth. 20,21 Due to the surface plasmon resonance of metallic nanoparticles under laser irradiation, monodispersed metallic particles with tunable particle sizes can be generated by laser irradiation at different wavelengths. 22,23 One of the advantages of pulsed-laser processing over conventional thermal annealing is that it only induces transient temperature increase at the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…Both thermal and plasma enhanced CVD can be used, almost always accompanied by decomposition of a hydrocarbon species in the presence of a transition metal catalyst; Ni or Fe being the most commonly used. In the CVD process the catalyst is pretreated by thermal heating [6,7] or laser nanostructuring [8] into islands. Such an approach tends to produce randomly arranged nanotubes which can have with a wide diameter distribution.…”
mentioning
confidence: 99%